An empirical evaluation of the pricing system of automobile insurance in Algeria - Rimi, Riadh; Latreche, Abdelouhab; Rimi, Okba (جامعة الوادي University of Eloued, 2015)
Le principal problème de l’assurance automobile en Algérie est le faible niveau des primes, déterminées par le ministère des Finances. Nous avons proposé, dans cette étude, de formaliser un modèle de tarification basé sur les caractéristiques des assurés (tarification a priori) et sur le nombre d’accidents passés des individus (tarification a posteriori) à l'aide d'un système Bonus-Malus. La méthodologie utilisée pour calibrer un système Bonus-Malus à la française, est celle proposée par (PITREBOIS, et al., 2003c). La comparaison entre le système de tarification appliqué par le ministère des Finances et le système théorique obtenu dans notre étude nous a permis de conclure que le système de tarification appliqué par le ministère des Finances n'est pas optimal. Abstract: The main problem of auto insurance in Algeria is the low level of the premiums, determined by the Ministry of Finance. We have proposed in this study, to formalize a pricing model based on the characteristics of the insured (pricing a priori) and the number of accidents went individuals (post pricing) using a system Bonus-Malus. The methodology used to calibrate a Bonus-Malus system in French, is that proposed by (PITREBOIS, et al., 2003c). The comparison between the tarification system applied by the Ministry of Finance and the theoretical system obtained in this study allowed us to conclude that the tarification system applied by the Ministry of Finance is not optimal
an approach with panel data
مقال- مجلة رؤى اقتصادية
Keywords: priori pricing, pricing posteriori, generalized estimating equations (GEE)models, BonusMalus system, panel data; tarification à priori, tarification à postériori, modèle des équations d'estimations généralisées(GEE), système Bonus-Malus, données des panel